NUMERICAL INVESTIGATION OF LAKE BED SEEPAGE PATTERNS: EFFECTS OF POROUS MEDIUM AND LAKE PROPERTIES - Genereux D.; Bandopadhyay I. (My University, 2001)
Three-dimensional steady-state numerical models were used to investigate the relative significance of several factors controlling lake bed seepage patterns: lake depth, lake bed slope, orientation of an asymmetric lake with respect to a regional hydraulic gradient, lake bed sediments, and heterogeneity and anisotropy of the porous medium. We considered both inflow and flow-through lakes, and our focus was on the details of seepage flux at the lake bed (not on the surrounding porous medium).While porous medium factors (anisotropy and heterogeneity) are important, we found several conditions where lake bed factors were nearly as important in controlling the distribution of seepage. Varying lake bed slope from 0.013 to 0.04 in different simulations had a significant effect on shoreline seepage (rates were 10-40% higher for lakes of low slope than lakes of steep slope). Also, significantly elevated seepage (in some cases, a local maximum) was observed offshore at the break in bed slope between the sloping side and flat central portions of the lake bed, whenever the surrounding porous medium had a high anisotropy (1000 or 100). For flow-through lakes in media of high anisotropy, the annual volume of groundwater inseepage was significantly higher (about 20%) in lakes with steep bed slope compared to those with low slope; this effect of slope was smaller at lower anisotropy. For an asymmetric flow-through lake (a lake with a steep bed slope on one side, moderate slope on the other) the percentage of lake bed experiencing inseepage was greatest when the steep side was downgradient, and the effect was larger at higher anisotropy. These effects illustrate the complex interaction between lake bed slope and the anisotropy of the surrounding porous medium in controlling lake:groundwater exchange.Adding low-conductivity lake sediments, and decreasing their conductivity, shifted groundwater seepage further offshore in inflow lakes; increasing the anisotropy of the surrounding porous medium had the same effect. Adding sediments and increasing anisotropy also decreased nearshore seepage in flow-through lakes, but without increasing offshore seepage; in this case, the net effect was a smaller annual volume of lake:groundwater exchange. At the same time, the percentage of the lake bed experiencing inseepage increased in flow-through lakes, even as the annual volume of inseepage was decreasing. Thus, for flow-through lakes, a larger area of inseepage may not be a good indicator of a greater volume of inseepage. Lake depth did not have a significant effect on the quantity or distribution of seepage to inflow or flow-through lakes. Many of the physical factors investigated here influence the amount of lake:groundwater exchange and the proportions of nearshore and offshore seepage; therefore, they are potentially significant to lake water quality and ecology in addition to hydrology.
Keywords: LAKE; GROUNDWATER; SEEPAGE; HYDROLOGY; SURFACE WATER; AQUIFER